Direct measurement of the effective electronic temperature in organic semiconductors - Kompatscher, Anton; Kemerink, Martijn (Physical review letters, 2025)
Organic semiconductors show complex phenomena due to their high energetic disorder. A striking example is the possibility of an increased effective temperature 𝑇eff of the charge carrier distribution relative to the lattice temperature, which results from the slow charge carrier relaxation after excitation, either by high electric field or photon absorption. The increased effective temperature has been linked to conductivity enhancements and performance increases in actual devices, but a direct observation has been lacking. Here, we utilize nanoscopic tree-terminal devices to measure the Seebeck voltage arising in a doped organic polymer semiconductor due to a field-driven enhancement of the effective electronic temperature, providing direct proof of the existence of 𝑇eff. The results agree quantitatively with numerical predictions by a kinetic Monte Carlo model. The findings not only provide fundamental understanding but also indicate an avenue toward low-loss thermoelectric devices.